Dynamic links between institutions, innovation and economic growth / Gopi Krishnan K.K.Vijayaraghavan - Gopi Krishnan , K.K.Vijayaraghavan (2019)
The thesis aims to investigate the dynamic links between institutions, innovation and economic growth. Innovation and institutional indices are constructed using nineteen indicators to test three main objectives at different income levels using definition from the World Bank. First is the causality direction between the variables; second, its short-run and long-run relationship and finally, the moderator role of institutions in enhancing the effectiveness of innovation activity on economic growth. The Toda-Yamamoto (1995) causality test shows that innovation and economic growth have a bidirectional relationship in High-Income Countries (HICs), but the same is not true for the Middle-Income Countries (MICs) and Low-Income Countries (LICs). Similarly, institutions and economic growth are found to have a unidirectional impact in the HICs running from institutions to economic growth. However, in the MICs and LICs, only institutional sub- indices show significant causal relationship. In MICs, the political institution tracks a two-way relationship with economic growth while in LICs, only the social institution influences economic growth. The thesis further investigates the short-run and long-run impacts by using the panel Autoregressive Distributed Lags (ARDL) Pooled Mean Group (PMG) estimator at different income level. For all income levels, in the short run, the impact of innovation and institutions on economic growth are generally insignificant. However, the impact on growth in the long run appears to be mostly significant. This suggests that the impact of institutions and innovation can only be realized in the long run. Innovation input is significant to economic growth for all income level. However, similar to causality, innovation index appears to be more beneficial to the HICs due to “founder effects” in the long run, whereas in MICs and LICs, only innovation input (not innovation output) is positively significant to economic growth. In other words, impact from innovation output may not be adequate to generate additional economic growth in MICs and LICs. It also suggests that MICs and LICs are still in the learning curve operating below the frontier technologies of the more advanced countries. As for the impact of institutions on economic growth, the relationship depends on the types of institution sub-indices and income level. For example, political institution drives economic growth in MICs but the same reduces economic growth in HICs. This relationship appears to be stronger when the role of institutions is moderated. The strengthening of political freedom enhances the impact of innovation activity on economic growth in MICs, but the reverse happens in the HICs. Given that the thesis finds different directional effect based on the income level, the empirical evidence is consistent with Barro’s (1996) argument on a non-linear relationship between political institution and economic growth. As for policy recommendation, this thesis suggests that policy makers consider income level and types of institutions in formulating growth policies.